Barriers between us : interracial sex in nineteenth-century American literature - Jackson, Cassandra, 1972- (Bloomington : Indiana University Press, 2004)
A vigorous discussion of 19th-century fiction about the role of racial ideology in the creation of an American identity.
Race and nation in nineteenth-century interracial fictions -- 1. The Last of the Mohicans or the First of the Mulattos? Slavery and native American removal in Cooper's American frontier -- 2. A land without names: national anxiety in The slave; or, Memoirs of Archy Moore -- 3. Reconstructing America in Lydia Maria Child's A romance of the republic and Frances E.W. Harper's Minnie's sacrifice -- 4. Doubles in Eden in George Washington's Cable's The grandissimes -- 5. "I will gladly share with them my richer heritage": schoolteachers in Frances E.W. Harper's Iola Leroy and Charles Chestnutt's Mandy Oxendine -- Formulating a national self.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: American fiction -- 19th century -- History and criticism; Racially mixed people in literature; Miscegenation in literature; Race in literature; LITERARY CRITICISM -- American -- General; American fiction; Miscegenation in literature; Race in literature; Racially mixed people in literature; Roman; Mulatten <Motiv>; Englisch; 1800-1899; Electronic books; Criticism, interpretation, etc; Electronic book